Cross-Cultural Adaptation and Validation of “Malocclusion Impact Questionnaire” into Moroccan Arabic - Farid Bourzgui; Samir Diouny; Hadam Mkhantar; Zineb Serhier; Mohamed Bennani Othmani (International Journal of Dentistry)
Introduction. The malocclusion index questionnaire (MIQ) is widely used in research and clinical practice. To our knowledge, there are no studies of its use in Moroccan patients. Aim. The objective of this study was to translate and culturally adapt the malocclusion impact questionnaire (MIQ) into Moroccan Arabic and to assess its reliability and validity among a sample of young Moroccan teenagers. The PIDAQ was cross-culturally adapted into Malay version by forward- and backward-translation processes, followed by psychometric validation. Materials and Methods. The MIQ was cross-culturally adapted into Moroccan Arabic by forward- and backward-translation processes, followed by psychometric validations. The MIQ was completed by a representative sample of 94 Moroccan adolescents aged 12–17 years selected randomly from five public schools of Casablanca. Internal consistency reliability was determined from Cronbach’s alpha, and the intraclass coefficient of the item scores was obtained in 1 month in a subset of 30 subjects. Data were analyzed using the Statistical SPSS software, version 16.0, SPSS Inc, Chicago, IL, USA. Results. The MIQ was completed twice by each participant at one-month interval to assess test reliability; the intraclass coefficient was r = 0.958, showing an excellent reproducibility. The internal consistency demonstrated the reliability of the questionnaire with Cronbach’s alpha coefficient of 0.917. The validity of the questionnaire was assessed by evaluation of the relationship between the total scores of the MIQ and normative need for orthodontic treatment according to ICON. The questionnaire showed an insignificant correlation (0.129, p<0.05). Conclusion. The Moroccan Arabic version of the MIQ was found to be reliable, whereas it has unacceptable validity according to ICON, and hence, it is unlikely to be a useful measure in orthodontic clinical trials for Moroccan adolescents.